Relationship between bronchopulmonary dysplasia phenotypes with high-resolution computed tomography score in early preterm infants - Yao, Qiong; Shen, Quan-li; Huang, Guo-ying; Hu, Xi-hong (Frontiers in Pediatrics, 2022)
Objective: To assess the relationship between high-resolution computed tomography (HRCT) abnormalities and clinical phenotypes of bronchopulmonary dysplasia (BPD). Methods: A retrospective, single-center study was carried out in Children’s Hospital of Fudan University between 2013 and 2020. Preterm infants born at ≤ 32 weeks’ gestation who were diagnosed with BPD and had HRCT between 40-50 weeks postmenstrual age were included in the study. HRCT images from six pulmonary lobes were scored based on 7 types of pulmonary lesions from two categories: the hyperaeration lesions and parenchymal lesions. The hyperaeration score (HS) included scores of decreased attenuation, mosaic attenuation, bulla/bleb, while parenchymal score (PS) included those of linear lesion, consolidation, bronchial wall thickening, and bronchiectasis. All 7 scores were summed up to create the total score (TS). One-way ANOVA testing or Kruskal-Wallis testing was adopted for the comparison of HRCT scores with BPD severity and clinical phenotypes. The correlation between HRCT scores and clinical phenotypes was evaluated by Spearman's correlation analysis. Results: A total of 81 cases were included in the study. Cases with more severe BPD had a higher TS (p = 0.01), HS (p = 0.02), PS (p = 0.02), mosaic attenuation score (p = 0.03), bulla/Bleb score (p = 0.03) and linear density score (p = 0.01). TS (r=0.28), PS (r = 0.35), linear density (r = 0.34) and consolidation (r = 0.24) correlated with PH. However, no HRCT score was significantly different between the patients with or without TBM. BPD patients with a combination of lung parenchymal disease, PH and TBM had the highest TS and HS. Conclusions: HRCT scores correlated with BPD severity and PH in our study. HS might be a useful tool in the assessment of BPD severity while linear densities and consolidation might be helpful in predicting PH.